Observations on Glucose Excursions With the Use of a Simple Protocol for Insulin, Following Antenatal Betamethasone Administration - Paulsen, Chané; Hall, David R.; Mason, Deidré; van de Vyver, Marí; Coetzee, Ankia; Conradie, Magda (Frontiers in Endocrinology, 2021)
Aims: Pregnant women with diabetes often require preterm delivery. Antenatal betamethasone reduces perinatal morbidity and mortality, but induces hyperglycemia. The primary objective was to observe glucose excursions and determine the preliminary safety of a protocol for subcutaneous insulin following betamethasone administration in an antenatal ward. Material and Methods: This retrospective study included all women with diabetes who received betamethasone due to imminent preterm delivery. Glucose excursions were evaluated in the fasting state and two-hours postprandial. Blood glucose values ≥14mmol/L or ≤3.5mmol/L were regarded as unacceptable hyper- and hypoglycemia respectively. Events over the first 96 hours were documented. Results: This study spanned 52 months and included fifty-nine women. Eleven episodes of defined hypoglycemia occurred in six women, all receiving insulin therapy, but none after a corrective dose of insulin. No serious hypoglycemic incident was reported. Seventeen women experienced hyperglycemic incidents almost entirely (47/56) within 48 hours of betamethasone administration, most often postprandially (34/56) and in 85% of episodes, preceded by pre-prandial values above 9 mmol/L (29/34). Fourteen (82.4%) of these women were receiving background insulin therapy. No case with gestational diabetes encountered defined hyperglycemia. Conclusions: This small study demonstrated preliminary safety of the protocol. Enhanced surveillance is necessary for 72 hours after initiation of betamethasone.